2016
DOI: 10.1177/1074248416653831
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Magnesium Treatment on Heart Rate Variability and Cardiac Ventricular Function in Diabetic Rats

Abstract: These results suggest that Mg treatment may attenuate diabetes-induced reduction in HRV and improve LV diastolic distensibility, without preventing hyperglycemia and dyslipidemia. Thus, Mg may have a modulatory role in the early stages of diabetic cardiovascular complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…It has been previously shown that the administration of magnesium as a supplement in rats in the early phase of diabetes leads to improved compliance of heart ventricles, as well as to the normalisation of the autonomous system of the myocardium, while the long-term effects of magnesium supplementation and their mechanisms remain unknown. 22 The aim of this study was to ascertain the effect of subchronic intake of magnesium hydrocarbonate -rich mineral water, as a form of magnesium supplementation, on cardiometabolic markers and electrolyte levels in rats with streptozotocininduced diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously shown that the administration of magnesium as a supplement in rats in the early phase of diabetes leads to improved compliance of heart ventricles, as well as to the normalisation of the autonomous system of the myocardium, while the long-term effects of magnesium supplementation and their mechanisms remain unknown. 22 The aim of this study was to ascertain the effect of subchronic intake of magnesium hydrocarbonate -rich mineral water, as a form of magnesium supplementation, on cardiometabolic markers and electrolyte levels in rats with streptozotocininduced diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…Blood used for Mg 2+ measurements was collected at the time of excision of the heart (24 hours after the final MgSO 4 or saline injection). The blood was centrifuged to obtain plasma, from which ionized Mg 2+ concentration was measured using photometric assays (Beckman AU, PathCare, SA) as previously described (Amoni et al 2017a).…”
Section: Plasma Mg 2+ Measurementsmentioning
confidence: 99%
“…Most frequently used duration for HRV in rat is 5 minutes that is similar to what is being used for analysis in humans. 2,3 Also, one minute, 4,5 3 minutes 6,7 and 10 minutes 8 durations are used often.…”
Section: Introductionmentioning
confidence: 99%